Factors Influencing Interest in Dive Tourism on Weh Island - Tianna Kinantasya; Rudy Pramono (Riviera Publishing, 2024)
Indonesia's diving tourism ranks second among the World's Best Diving Destinations, according to Scuba Diving magazine readers' choices in 2019. Weh Island, in particular, is noted for its significant potential in diving tourism. This study aims to empirically evaluate the impact of attraction, facilities, and accessibility on diving interest at Weh Island. The research targeted individuals with diving certifications, using purposive sampling to gather responses from 97 participants. A quantitative approach was employed, utilizing SmartPLS software for analysis. The results indicate that attraction has a direct positive effect on diving interest, with a significance value of 0.001 (<0.05), suggesting that an increase in attraction leads to a 42.4% rise in visiting interest. Similarly, facilities also have a direct positive effect on diving interest, with a significance value of 0.000 (<0.05), implying that improved facilities result in a 35.3% increase in visiting interest. The implications of this study highlight the important role of attractions and facilities in increasing diving interest. This implies that improving these factors can significantly increase tourist interest in Weh Island. Stakeholders in the dive tourism sector should focus on improving attractions and facilities to increase this potential and attract more divers. Further research could explore the impact of accessibility and other factors on dive tourism to provide a more comprehensive understanding of tourist interest.